Evaluation of Shooting Drill Training on the Shooting Accuracy of UNM BKMF Basketball Athletes - Suwardi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to evaluate the effectiveness of shooting drill training on improving shooting accuracy of athletes from the Student Coordination Board of the Faculty of Sport Science (BKMF) Basketball, Makassar State University (UNM). The study used a descriptive qualitative approach with a case study design, involving 12 main male athletes of BKMF UNM as participants. The research instruments included video observation of shooting motion analysis, in-depth interviews with coaches and athletes, documentation of pre- and post-training shooting accuracy data, and field notes from 12 training sessions over 6 weeks. The research procedure included a shooting accuracy pretest (mid-range jump shot 10 shots per athlete), shooting drill training intervention (3 sessions/week, 60-90 minutes/session with 75-100 repetitions), and a shooting accuracy posttest. Data analysis used triangulation of sources and methods with thematic analysis techniques. The results showed an average increase in shooting accuracy of 28.5% from 62.3% (pre) to 80.8% (post), with individual variation of 22-36%. Key themes included improved consistency of follow-through movements (85% of athletes), increased muscle memory (92% of athletes), and reduced variability in throwing angles (standard deviation reduced by 12.4°). Identified challenges included fatigue with repetitions of more than 75 shots and the need for individual visual feedback. The study concluded that shooting drills effectively improved shooting accuracy among BKMF UNM athletes by strengthening automatic movement patterns and technical consistency, with recommendations for optimizing training volume and integrating feedback technology for maximum results.